Acerola polysaccharides ameliorate high-fat diet-induced non-alcoholic fatty liver disease through reduction of lipogenesis and improvement of mitochondrial functions in mice. Issue 1 (10th December 2019) - Hu, Yuanyuan; Yin, Fawen; Liu, Zhongyuan; Xie, Hongkai; Xu, Yunsheng; Zhou, Dayong; Zhu, Beiwei
Abstract : Acerola polysaccharides ameliorate HFD-induced NAFLD by inhibiting lipogenesis, reducing oxidative stress and inflammation, and promoting the mitochondrial function in C57BL/6 mice. Abstract : Acerola polysaccharides (ACPs) were purified from acerola ( Malpighia emarginata DC.), a tropical fruit with strong antioxidant and anti-inflammatory activities. However, the biological activities of ACPs have barely been investigated. The present study was designed to investigate the efficacy of ACPs in the treatment of high-fat diet (HFD)-induced nonalcoholic fatty liver disease (NAFLD) in C57BL/6 mice. Male C57BL/6 mice were fed with a high-fat diet and treated with different doses of ACPs for 9 continuous weeks. NAFLD was examined in terms of body weight, lipid profiles, liver function markers, and histology. Gene expression was determined by using both qRT-PCR and western blot. Our results showed that administration of ACPs significantly reduced HFD-induced hyperlipidemia and hepatic lipid deposition by inhibiting the SREBP1c pathway in mice. ACP treatment normalized oxidative stress by activating nuclear factor (erythroid-derived-2)-like 2 (Nrf2) and reduced the expressions of pro-inflammatory cytokines in HFD fed mice. Furthermore, ACPs reduced uncoupling protein 2 (UCP2) expression, restored mitochondrial ATP content, increased mitochondrial complex I, IV, and V activity, and increased mitochondrial beta-oxidation by stimulating peroxisomal proliferator-activated receptor-gamma coactivator-1α (PGC-1α) in the liver of HFD-fed mice. Our study indicated that ACPs may be an effective dietary supplement for preventing HFD-induced NAFLD by regulating lipogenesis, reducing inflammation and oxidative stress, and promoting the mitochondrial function.